Aptasensors: Amplification of Resonant Rayleigh Light Scattering Response Using Immunogold Colloids for Detection of Lysozyme (Small 20/2013). Issue 20 (18th October 2013) - Truong, Phuoc Long; Choi, Seung Phill; Sim, Sang Jun
<x xml:space="preserve">Abstract</x> An individual nanoplasmonic aptasensor is effectively exploited to detect lysozyme utilizing its adsorption on a DNA aptamer bound to a Au nanoparticle and its interaction with an antibody bound to another Au nanoparticle. S. J. Sim and co‐workers report on page 3485 that the optical plasmonic resonance coupling of the larger Au nanoparticle with the smaller immunogold colloids causes a strong resonance peak shift and the light scattering color changes (green to red) of corresponding nanoparticles under the incident light (white) of the dark‐field microscope. An increase of up to 380% in the LSPR λmax shift is demonstrated compared to the non‐coupling shift. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>